2015
DOI: 10.1002/2015rs005725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of observed and predicted MUF(3000)F2 in the polar cap region

Abstract: The maximum usable frequency for a 3000 km range circuit (MUF(3000)F2), computed from ionosonde measurements at Resolute (74.75 Predictions and observations show diurnal and seasonal variations; however, the VOACAP and ICEPAC models fail to reproduce the diurnal variation trend observed in the measurements during the summer period. The performance of these models has been statistically analysed: REC533 gives a better performance in winter and equinox months, while VOACAP has a better performance for both equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
0
13
0
2
Order By: Relevance
“…Themens et al [2013] demonstrated that the sparsity of data in high-latitude regions contributes to significant errors in the representation of TEC in these regions by global TEC maps, and Themens et al [2015] showed that the strong gradients in TEC at high latitudes significantly degrade the performance of standard Global Positioning System (GPS)-based TEC calibration techniques. Also, Athieno et al [2015] and Athieno and Jayachandran [2016] show that standard HF communication models exhibit significant errors at high latitudes, largely due to errors in the URSI and International Radio Consultative Committee critical frequency maps, which are also used in the IRI. All of these studies highlight the need for a new representation of the high-latitude ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Themens et al [2013] demonstrated that the sparsity of data in high-latitude regions contributes to significant errors in the representation of TEC in these regions by global TEC maps, and Themens et al [2015] showed that the strong gradients in TEC at high latitudes significantly degrade the performance of standard Global Positioning System (GPS)-based TEC calibration techniques. Also, Athieno et al [2015] and Athieno and Jayachandran [2016] show that standard HF communication models exhibit significant errors at high latitudes, largely due to errors in the URSI and International Radio Consultative Committee critical frequency maps, which are also used in the IRI. All of these studies highlight the need for a new representation of the high-latitude ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of such tireless efforts, recent studies by Themens et al [2014] and Themens and Jayachandran [2016] still show persistent limitations of the IRI at high latitudes especially in the polar cap. Previous research has also emphasized the disadvantage of data scarcity to the exploration of the polar ionosphere especially in the empirical modeling and prediction of important HF and ionospheric parameters [e.g., Oyeyemi and McKinnell, 2008;Themens et al, 2014;Athieno et al, 2015]. The Canadian High Arctic Ionospheric Network (CHAIN), an array of ground-based radio instruments deployed and operated by the University of New Brunswick, has made a tremendous improvement in data availability especially in the high arctic which includes the polar cap region [Jayachandran et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The International Reference Ionosphere (IRI) is the accepted standard for the climatological representation of the ionosphere by the International Organization for Standardization (ISO) [ Bilitza et al , ]. It is regularly applied in ionospheric assimilation frameworks [ Komjathy and Langley , ; Komjathy et al , ; Hernandez‐Pajares et al , ; Bust et al , ; Schmidt et al , ; Zeilhofer et al , ; Pezzopane et al , ; Galkin et al , ], in radar altimetry [ Ovodenko et al , ], in theoretical ring current models [ Ebihara et al , , ], and in high‐frequency (HF) communications forecasting [ Jodalen et al , ; Settimi et al , ; Athieno et al , ]. While several studies speak to the accuracy of the IRI at midlatitude and low latitude [ Sethi et al , ; Ehinlafa et al , ; Ezquer et al , ; Bilitza et al , ; Wichaipanich et al , ], the same cannot necessarily be said for its application to high‐latitude regions, where transport and particle precipitation events dominate ionospheric variability for large portions of the year [ Carlson , ; MacDougall and Jayachandran , ; Jayachandran et al , , ].…”
Section: Introductionmentioning
confidence: 99%